Emergency department 'outbreak rostering' to meet challenges of COVID-19. Issue 7 (28th May 2020) - Chua, Wei Lin Tallie; Quah, Li Juan Joy; Shen, Yuzeng; Zakaria, Diana; Wan, Paul Weng; Tan, Kenneth; Wong, Evelyn
Abstract : The COVID-19 outbreak has posed unique challenges to the emergency department rostering. Additional infection control, the possibility of quarantine of staff and minimising contact among staff have significant impact on the work of doctors in the emergency department. Infection of a single healthcare worker may require quarantine of close contacts at work. This may thus affect a potentially large number of staff. As such, we developed an Outbreak Response Roster. This Outbreak Response Roster had fixed teams of doctors working in rotation, each team that staff the emergency department in turn. Members within teams remained constant and were near equally balanced in terms of manpower and seniority of doctors. Each team worked fixed 12 hours shifts with as no overlapping of staff or staggering of shifts. Handovers between shifts were kept as brief as possible. All these were measures to limit interactions among healthcare workers. With the implementation of the roster, measures were also taken to bolster the psychological wellness of healthcare workers. With face-to-face contact limited, we also had to maintain clear, open channels for communication through technology and continue educating residents through innovative means.